Technoculture : the key concepts - Shaw, Debra Benita (Key concepts (Berg (Firm)), 2008)
Explores the power of scientific ideas, their impact on how we understand the natural world and how successive technological developments have influenced our attitudes to work, art, space, language and the human body.